Sistem Informasi Perpustakaan SMP Yos Sudarso Cigugur Menggunakan Bahasa Pemrograman PHP dan Database MYSQL - Panji Novantara; Damasus Sandi Setiadi (JEJARING : Jurnal Teknologi dan Manajemen Informatika, 2019)
SMP Yos Sudarso Cigugur is one of the schools under the auspices of “Yayasan Salib Suci” Fondation. At present there are several problems in the process of library services. this starts from the process of recording member data, recording transactions, recording book data and calculating fines that are still using conventional methods. The purpose of this study is to determine the course of the system, create a system design, test the system created and implement the system created. The purpose of this research is to find and provide solutions to existing problems regarding library services. The method used in this study uses a waterfall, where this method has the characteristics of activities that flow from one phase to the next. The programming language that researchers use is the PHP programming language with MySql database. The results of research conducted by the author shows the system created can help library services at Yos Sudarso Cigugur Middle School. Further research development is expected to have a flexible information system built in a mobile form and integrated with the internet.